178 The Effect of Fleshing Ability on Cow and Calf Performance - Holder, Amanda (J Anim Sci, 2019)
Several factors influence the overall maintenance requirements of a mature beef cow including age, gain, lactation, pregnancy, and fleshing ability. However, limited research is available to distinguish what sets a hard-fleshing cow apart from an easy-fleshing cow. Cows that are hard-fleshing maintain a lower body condition score (BCS) throughout the year compared to easy-fleshing counterparts. The objectives of this experiment are to determine the differences in characteristics and production between cows classified as easy- vs. hard- fleshing. Characteristics of interest include feed intake, milk yield, milk composition, body weight changes, BCS changes, and other body composition measurements, as well as calf weaning weight. In this study, 24 spring-calving, mature Angus beef cows were classified as either hard-fleshing or easy-fleshing based on BCS and ultrasound measurements for back fat and rump fat. The intake study took place during the second trimester, cows were assigned to an easy- or hard-fleshing pen based on treatment where they remained for the entirety of the 45-day intake study. Each treatment was replicated three times in a completely randomized design. Milk data collection began one month after calving with monthly milkings from May—August. There were no differences (P = 0.9) in DMI, although hard-fleshing cows had greater DMI calculated on a metabolic body weight basis (P = 0.05). There was a trend (P = 0.12) for hard-fleshing cows to wean heavier calves, although there was no difference in mean milk yield (P = 0.44). Body condition score was positively correlated with protein and carbohydrate content of milk with easy-fleshing cows having greater contents of both (P = 0.02 and P < 0.01, respectively). Overall, an increase in BCS without an increase in DMI may be beneficial from a reproductive standpoint, though more research in this area is needed.